Kontribusi Permainan Tradisional Terhadap Keterampilan Motorik Kasar Siswa: Classroom Action Research - Ramkar, Rahma Sakura; Septiadi, Firman; Bachtiar, Bachtiar (PT Mediatama Zayna Indonesia, 2024)
This study aims to evaluate the contribution of traditional games to the development of gross motor skills in students at Kawakib Islamic Elementary School (SDI). The research employs the Classroom Action Research (CAR) method with a sample size of 18 students. The study is conducted in two cycles, observing the progress of students' gross motor skills in each cycle. The results indicate a significant improvement in students' gross motor skills after the implementation of traditional games. In cycle I, 10 students (55.56%) did not show significant progress, while 5 students (27.78%) were still in the initial stages of development, and 3 students (16.67%) achieved development criteria as expected. However, in cycle II, there was a very significant improvement, with 15 students (83.33%) achieving very good development criteria and 3 students (16.67%) achieving development criteria as expected, with no students remaining in the categories of not developing or just starting to develop. This research demonstrates that traditional games have a positive contribution to the development of gross motor skills in students at SDI Kawakib.